Dead man's list - Rose, Karen, 1964- (Rose, Karen, 1964- San Diego case files, 2025)
"On a long-anticipated second date with police psychologist Dr. Sam Reeves--right as things are getting steamy--Kit stumbles across the mutilated body of a local San Diego politician. The politician is loved by many of his constituents but is hated and reviled by many more. That the suspect list is long is no surprise to anyone, but exactly who ends up on it stuns Kit and her team. As the SDPD reveal the victim's sinister dealings, Kit and Sam are forced to navigate the lawless world of the city's most rich and powerful citizens to find answers. But time is rapidly running out, with their sources of information dropping like flies as the killer methodically eliminates loose ends--and anyone else who stands in the way"--